Time Management for Better Job Performance: An Analysis from Al-Wasatiyyah Perspective - Rafikul Islam; Md. Yousuf Ali; Noor Mohammad Osmani (Asian Academy of Management Journal, 2021)
Managing time means engaging activities that generate greater benefits to human beings. To a Muslim, benefits encompass for both worlds, i.e., life in this mundane world as well as life in the hereafter. Previous research on time management resulted in a variety of findings depending on the aspects under study. The objective of this research is to investigate the components of time management that have significant relationship with job performance, especially in the context of Malaysian employees. This research also intends to relate the concepts and attributes of “al-wasatiyyah” that have direct relationship to job performance. To pursue the research objectives, 223 employees working in different sectors in Malaysia were contacted. The researchers found that certain time management factors namely “prioritisation of tasks,” “usage of schedules,” and “time management instrument” sustained statistically significant positive relationships to job performance. Meanwhile, the al-wasatiyyah variables that have been found to have statistically significant positive relationships to job performance are “working with sincerity/pure intention (niyyah),” “following the middle path to avoid excessiveness in working place (wasatan),” “practicing values in working place (qiam),” and “ensuring fairness in task assignment (adl).” These findings have important implications. Most importantly, managers of organisations can practice them to motivate employees in order to enhance their job performance which by and large will improve the performance of the whole organisation in the long run.